Vertical patterns of metabolism in three contrasting stratified lakes. (20th June 2014) - Obrador, Biel; Staehr, Peter A.; Christensen, Jesper P. C.
Abstract : Recent advances in open‐water measurements suggest significant temporal and spatial variability of gross primary production (GPP), net ecosystem production (NEP), and respiration (R) with implications for understanding carbon cycling in lakes. This study applied high‐frequency depth profiles in three stratified lakes of different trophic status to investigate (1) the importance of vertical variations in metabolic rates, (2) the effects of changes in the depth of the mixed layer (Zmix ) and the photic zone (Zeu ), and (3) the photoacclimative responses of the aquatic autotrophs to changes in these conditions. Taking account of vertical differences in metabolism improved the reliability of whole‐areal NEP estimates during stratification. Whereas the hypolimnion was always heterotrophic, and the epilimnion was mostly autotrophic, the metalimnion had NEP > 0 when Zeu > Zmix . Although most of GPP and R occurred in the epilimnion, between 0% and 20% of GPP and 4% and 37% of R took place in the metalimnion. Areal metabolic estimates based on surface measurements deviated up to 60% for GPP and 80% for R when Zeu > Zmix . The vertical variability in metabolism was driven by available light in both the epi‐ and metalimnion. Coupling between GPP and R was low in all layers and indicated increasing background R with depth. Light utilization efficiency was significantly higher under low light conditions, indicating photophysiological acclimation of phytoplankton to decreasing light in the metalimnion.